Exciplex emissions derived from exceptionally long-distance donor and acceptor molecules. Issue 40 (23rd September 2019) - Pu, Yong-Jin; Koyama, Yuki; Otsuki, Daisuke; Kim, Minjun; Chubachi, Hiroya; Seino, Yuki; Enomoto, Kazushi; Aizawa, Naoya
Abstract : We report exceptionally long-distance coupled exciplex emissions between electron-donor and electron-acceptor molecules even with a 70 nm-thick spacer layer. Abstract : Intermolecular electron–hole coupling in organic semiconductor excited states plays important roles in organic light-emitting diodes and organic photovoltaics, and the distance of the coupling is typically only on the order of a few nanometers. Here, we report exceptionally long-distance coupled exciplex emissions between electron-donor and electron-acceptor molecules even with a 70 nm-thick spacer layer. Donor/spacer (∼70 nm)/acceptor-type stacked films showed a low-energy band emission, which is not ascribed to the emission of the donor, spacer, and acceptor themselves, but well corresponds to the energy difference between the highest occupied molecular orbital of the donor and the lowest unoccupied molecular orbital of the acceptor. Delayed transient photoluminescence (PL) and electroluminescence (EL) decays and PL quenching by oxygen at the low-energy band were observed and are consistent with the characteristics of the exciplex species.